The characterization of health groups implemented by family health teams and Nasf-AB in a regional in the Municipality of Jaboatão dos Guararapes (Research, Society and Development, 2020)
Objective: to characterize health groups in a Regional Health Center in Jaboatão dos Guararapes. Methodology: This is a qualitative, transversal research of an exploratory and explanatory character. Data were collected using a semi-structured electronic form, covering the following topics: description of health groups; motivation for the development of groups; relationship between the family health team (eSF) and Nasf-AB vis-à-vis the groups; main practices developed in the groups; professionals who actively participate in the face of group practices and infrastructure for the realization of groups. The data were analyzed according to Bardin's content analysis technique. Results: The sample consisted of 16 professionals from the eSF and Nasf-AB team, all female, considering the professions of CHA, nurse, dentist, speech therapist, psychologist, social worker and physiotherapist. Final considerations: there are a large number of health groups implemented according to the demands of the territory and with different approaches, with the difficulty of lack of adequate infrastructure for the performance of collective practices, being carried out through meetings between family health teams and Nasf-AB, since Nasf-AB professionals play an important role in leading most groups.